Seriatopora Diversity Preserved in Upper Mesophotic Coral Ecosystems in Southern Japan - Sinniger, Frederic; Prasetia, Rian; Yorifuji, Makiko; Bongaerts, Pim; Harii, Saki (Frontiers in Marine Science, 2017)
Coral reefs worldwide are facing increasing stress due to drastic changes in their environment. Mesophotic coral ecosystems (MCEs) have been considered as a potential refuge from several major stressors, such as warm-water bleaching events. However, their role as a subsequent source of larvae remains unclear for many species, particularly as genetic differentiation of corals over depth has frequently been observed. In 1998 and 2001, two severe bleaching events around Okinawa Island in Japan resulted in major changes to the shallow reefs, including the local “extinction” of species such as Seriatopora hystrix at Sesoko Island. However, recently this species was found to be present in abundance at mesophotic depths in the area, despite no clear signs of recovery being observed in the adjacent shallow waters. Here, we assessed the genetic diversity of Seriatopora from this deep population and provide a comparison with populations from shallow to mesophotic depths in other parts of the Ryukyu archipelago, to understand their depth specificity and their importance in genetic diversity conservation of affected shallow populations. High levels of genetic diversity were observed in both shallow and mesophotic Seriatopora populations for both the nuclear (internal transcribed spacer 2, ITS2) and the mitochondrial (hypervariable open reading frame, ORF) marker, with no clear partitioning of haplotypes over depth or across locations in the archipelago. Both ITS2 and ORF suggest the presence of potential cryptic species and the discrepancy between the markers could reflect hybridization or incomplete lineage sorting. Although associated endosymbionts (Symbiodinium spp.) all shared the same mitochondrial haplotype (cytochrome oxidase subunit 1, COI), the nuclear ribosomal ITS2 revealed slight potential habitat partitioning between the genotypes, with a small decrease of C59 Symbiodinium types below 10 m depth and a mirrored increase in C1/C78a-related types. The relative absence of depth-specific host lineages and the substantial overlap between shallow and deep Symbiodinium types indicate that Okinawan MCEs may act as a refuge preserving genotypic diversity of bleaching-sensitive coral such as Seriatopora, and on the long-term may have the potential to contribute to shallow-water recolonization of this species.